2019
DOI: 10.14419/ijet.v8i4.29742
|View full text |Cite
|
Sign up to set email alerts
|

Steel framed structures with cross laminated timber infill shear walls and semi-rigid connections

Abstract: In recent years, hybrid steel-timber structures are seeing an increasing use in modern building construction at a competitive price. Cross-laminated timber (CLT) is a prefabricated multi-layer engineered panel wood product, manufactured by gluing layers of solid-sawn lumber at perpendicular angles. Their orientation results in excellent structural rigidity in both orthogonal directions. CLT construction materials are used not only for flooring systems and roof assemblies, but CLT infill shear walls are also ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…For the convenience of the design, two of the parameters are combined together. A new parameter α E is defined in Equation (7). It is named the self-centering ratio.…”
Section: Influences Of the Lateral Wall-to-frame Stiffness Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…For the convenience of the design, two of the parameters are combined together. A new parameter α E is defined in Equation (7). It is named the self-centering ratio.…”
Section: Influences Of the Lateral Wall-to-frame Stiffness Ratiomentioning
confidence: 99%
“…With the advantages of wood material, timber structure has been earning increasing attention in recent decades. A lot of research has been focused on making timber structure more applicable to mid-rise or even high-rise buildings [3][4][5][6][7]. The hybridization between timber and steel material is one of the research hotspots [8].…”
Section: Introductionmentioning
confidence: 99%
“…Seismic performance can similarly be enhanced by combining materials to optimise ductility, strength, and stiffness, all of which contribute to the dynamic structural behaviour of buildings (Quintana Gallo and Carradine, 2018). The most popular concepts of steel-timber hybrid systems are the steel frame with CLT shear walls (Dickof et al, 2014;Tesfamariam et al, 2014;Vogiatzis et al, 2019) and the timber frame with steel plate shear walls, (Conrad and Phillips, 2019;Igbal et al, 2020), the former concept is the focus of this work. Please note that in this as well as the following sections, unless otherwise stated, the abbreviation STSW refers to the concept of steel frame with CLT shear walls, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned tested hybrid system was numerically investigated by (Li et al, 2014), and further developed with a post-tensioned steel frame and light frame wood shear wall by (Cui et al, 2020). Recently, a hybrid system composed of steel frames with semirigid connections and CLT shear walls was designed and analyzed by the authors (Vogiatzis et al, 2019), although the post-elastic phase was not considered in that work.…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropic nature of the wood in order to be simulated as an orthotropic material model requires a number of independent material properties which are difficult to measure and usually, they are not reported in the available publications. It is common among scholars to simplify the input values for radial and tangential direction, this can also be seen on the numerical modelling of hybrid steel framed with cross laminated timber infill shear walls -STSW [13], bolted hybrid connections [14], steel-timber composite floors [15], and hold-down connections for masstimber buildings [16]. From the available literature, it appears that although some reported experimental studies could be found in [2], very limited analytical or numerical investigation was reported on the behaviour of wood-steel composite shear wall systems.…”
Section: Introductionmentioning
confidence: 99%